Utilization of Crab Shells as Calcium Flour and Its Application in Processed Fish Nuggets: Pemanfaatan Cangkang Rajungan Sebagai Tepung Kalsium Dan Aplikasi Dalam Olahan Nugget Ikan - Dewi Kartika Sari; Salsa Bila Qolda Rahman; Rosfia Wahdini; Aditya Dwiprastana; Gazali Rahman; M. Nazar Anugerah (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
The purpose of the 2025 Impactful Thematic KKN activity of FPIK ULM is for students to learn about society, explore problems, especially in the fisheries and maritime sector in Sungai Lembu Village, and participate in providing solutions to address these problems. Sungai Lembu Village is located in Kusan Hilir District, Tanah Bumbu Regency, South Kalimantan. This village has a fairly large amount of crab shell waste. The impact of environmental pollution due to crab shell waste is not managed properly. Increasing the added value of shell waste can be a solution to overcome shell pollution on the environment in addition to being an opportunity to increase community income. From the results of the KKN activity, the potential for large crab shell waste provides an opportunity for the availability of raw materials for calcium flour processing. Flour made from crab shells has a calcium content of 133.57 mg/g or 13.36%. This flour is an intermediate product that can be applied in processed fishery products with high protein and calcium characteristics. The resulting processed product is fish nuggets fortified with crab shell flour.